ELECTRIC CIGARETTES’S EFFECT TO THE MDA LEVELS IN BLOOD OF WISTAR RAT - Etha Rambung (HUMAN CARE JOURNAL, 2020)
The use of electronic cigarettes (e-cigarettes) has spread widely and increased dramatically among young people aroud the world. Variations in product design, taste, and marketing patterns increase the young people's interest in electronic cigarettes. Even many electric cigarettes are sold in shoppinng cebters and online, so they are easy to reach by teenagers. This study aims to analyze oxidative stress due to exposure to e-cigarettes by assessing the difference in blood MDA levels in the control and treatment groups. The method used is the Posttest Only Control Group Design. Thirty two male wistar rats divided into four treatments goups: K1 (SC (-), EE (-)), K2 (SC (-), EE(-)), P1 (SC(-),  EE (+) 15 times), and P2 (SC (-), EE (+) 30 times). The treatment is given for 5 minutes/ day for 50 days. Termination was carried out on the 50th day using ketamine. Intracardial blood sampling for examination of MDA levels by the TBARS method. The data obtained were tested by Kruskal Wallis with a significance of p <0.05. MDA blood levels in P2 were significantly higher than P1 (p =0,035), K2 (p =0,001) and K1 (p =0,001). This study shows that e-cigarettes can cause oxidative stress in experimental animals.